1999
DOI: 10.1029/1999gl008361
|View full text |Cite
|
Sign up to set email alerts
|

High resolution measurements of absolute thorium abundances on the lunar surface

Abstract: Abstract. The Lunar Prospector (LP) Gamma-Ray Spectrometer (GRS) has been used to map the global abundance of thorium on the lunar surface. A global map of absolute thorium abundances on a 2 ø by 2 ø equal-area pixel scale is presented using new detector modeling results and low altitude LP data. Because thorium is relatively abundant in KREEP-rich material, these data provide fundamental information regarding the locations and importance of terranes that are rich in KREEP bearing materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
97
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 16 publications
4
97
0
Order By: Relevance
“…The three white circles represent the Imbrium, Nubium, and Grimaldi basins in order of decreasing size. The map is in a Lambert equal-area projection, extending from 120øW to 30øE and 90øS to 90øN and centered on 30øW 100øE) between the craters Belkovich (63øN, 90øE) and Compton (55øN, 105øE) (-10 ppm) [Lawrence et al, 1999].…”
Section: Mare P•xelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The three white circles represent the Imbrium, Nubium, and Grimaldi basins in order of decreasing size. The map is in a Lambert equal-area projection, extending from 120øW to 30øE and 90øS to 90øN and centered on 30øW 100øE) between the craters Belkovich (63øN, 90øE) and Compton (55øN, 105øE) (-10 ppm) [Lawrence et al, 1999].…”
Section: Mare P•xelsmentioning
confidence: 99%
“…Here the Th map is merged with a shaded relief map to allow the association of morphologic with compositional features. The absolute Th abundance is based on total counts per 32 seconds in the spectral region of the main 232Th y-ray (2.61+0.1 MeV) [Lawrence et al, 1999], and these counts have been corrected for gain, dead time, cosmic-ray variations, and asymmetric response of the instrument. The map is in a Lambert equalarea projection, extending from 120øW to 30øE and 90øS to 90øN and centered on 30øW.…”
Section: Introductionmentioning
confidence: 99%
“…The set from Clementine is the visible albedo using the 750 nm wavelength band of the UV/VIS camera [Lucey et al, 1994]. The four from Lunar Prospector include the abundance of thorium, [Th] [Lawrence et al, , 1999, the abundance of FeO, [FeO] Prettyman et al, 2001], the ratio of epithermal to thermal neutrons, [E/T] , and the flux of fast neutrons, [FN] Maurice et al, 2000]. Two of these sets provide a relatively direct measure of the composition of an element ([FeO] and [Th]), and the remaining three provide an index, which is indirectly related to the abundance of FeO, TiO 2 , and thorium, through a host of chemical associations that are observed in returned samples [see, e.g., Haskin and Warren, 1991, and references therein].…”
Section: Data Sets and Methods Of Analysismentioning
confidence: 99%
“…This survey showed that enhanced surface abundances of U, Th, and K were confined mostly to the near side of the Moon in the vicinity of Oceanus Procellarum and the Imbrium basin. A later extension to include the entire lunar surface was afforded with data returned by the Lunar Prospector Gamma-Ray Spectrometer [Lawrence et al, , 1999, which provided conclusive proof that the Procellarum-Imbrium region is indeed a unique province of enhanced Th composition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation